2011
DOI: 10.1016/j.virusres.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

In situ apoptosis of adaptive immune cells and the cellular escape of rabies virus in CNS from patients with human rabies transmitted by Desmodus rotundus

Abstract: The aim of the current study was to investigate the apoptosis of neurons, astrocytes and immune cells from human patients that were infected with rabies virus by vampire bats bite. Apoptotic neurons were identified by their morphology and immune cells were identified using double immunostaining. There were very few apoptotic neurons present in infected tissue samples, but there was an increase of apoptotic infiltrating CD4+ and TCD8+ adaptive immune cells in the rabies infected tissue. No apoptosis was present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…The correlation between pathogenesis and apoptosis is consistent with observations of apoptosis in inflammatory cells, microglia and macrophages in natural RABV infections in humans and dogs [23,79]. Therefore, non-lethal strains are cleared from the CNS by infiltrating T cells—despite evidence of RABV antigen in the brain—whereas lethal strains destroy these T cells and are thus free to replicate and spread throughout the CNS [56,87,90]. In support of this hypothesis, several apoptotic pathways are involved in RABV infections that have specific ligands and receptors directly involved with the destruction or inhibition of T cells.…”
Section: Apoptosis: Detrimental or Beneficial To The Host?supporting
confidence: 82%
See 1 more Smart Citation
“…The correlation between pathogenesis and apoptosis is consistent with observations of apoptosis in inflammatory cells, microglia and macrophages in natural RABV infections in humans and dogs [23,79]. Therefore, non-lethal strains are cleared from the CNS by infiltrating T cells—despite evidence of RABV antigen in the brain—whereas lethal strains destroy these T cells and are thus free to replicate and spread throughout the CNS [56,87,90]. In support of this hypothesis, several apoptotic pathways are involved in RABV infections that have specific ligands and receptors directly involved with the destruction or inhibition of T cells.…”
Section: Apoptosis: Detrimental or Beneficial To The Host?supporting
confidence: 82%
“…There have been observations of mild numbers of inflammatory cells, macrophages and oligodendrocytes, as well as a large number of infiltrating T cells, undergoing apoptosis in infected tissues during natural RABV infection [87,88,89], suggesting that these may be the targets of RABV-induced apoptosis. The inherent differences in pathogenicity between non-lethal and lethal strains of RABV may be due to the ability of non-lethal strains to induce apoptosis in neurons, as opposed to the lethal strains inducing programmed death in infiltrating T cells (Figure 1) [56,82,87,90,91], as fewer infiltrating lymphocytes have been detected in the brains of animals infected with pathogenic strains [92]. Similarly, HIV has been shown to sensitize T cells to tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL)- and CD95(Fas/APO-1)-ligand (CD95L)-mediated apoptosis [93].…”
Section: Apoptosis: Detrimental or Beneficial To The Host?mentioning
confidence: 99%
“…What impact these cytokines have on neuronal integrity is unclear. Though CD8+ T cells have been found in brain sections of human rabies victims [50], their deletion appears to have no significant effect on the survival of challenged mice [4].…”
Section: Discussionmentioning
confidence: 99%
“…28 This inefficacy occurs because the virus can induce a significant production of calcitonin, somatostatin, and vasoactive intestinal peptides in infected cells, thus limiting the activity of T cells 29 ; further, the virus can even induce T cell apoptosis 30,31 Immunohistochemical studies of RABV-infected brains and spinal cords demonstrated that neurons showed a large amount of RABV antigen with intact morphology and that migrating T cells showed evidence of undergoing the apoptotic process. 30,32,33 In contrast to infections caused by highly pathogenic strains, T cells are important in controlling those caused by attenuated viruses, in which infected neurons are successfully eliminated by apoptosis and T cells remain intact. 9,34,35 Differences in the pathogenicity of RABV strains are associated not only with viral replication and the cellular infection rate but also with the level and duration of cytokine expression, in addition to the induction of apoptosis in immune cells.…”
Section: Introductionmentioning
confidence: 99%